Sistem Pakar Penentuan Tanaman Obat pada Penyakit THT berbasis Web - Pebriyanti, Ni Kadek; Andika, Ary Wira (LPPM STMIK STIKOM Indonesia, 2018)
With the use of technology in the world of health, facilitate the public in obtaining information. In this case, handling of mild ENT disease can be done with the initial handling that is utilizing medicinal plants as one good alternative. However, lack of information obtained, resulting in less people know what medicinal plants that can be utilized. Therefore, it is necessary to build a system that is educative by providing information of ENT and medicinal diseases of any medicines that can be utilized in the follow up of ENT disease in suffering. This system also provides information on medicinal plants outside of ENT diseases.